Akkadian kīam ~ kī(ma): Syntactic and Semantic Relationships - Kohēn, ʿErān (Orientalia, 2024)
The common Akkadian similative particles kīma (‘as, like, instead of’; ‘as soon as, when; that; because; so that’) and kīam (‘this way; in this manner’) are strikingly multifunctional. kīam is a manner demonstrative whereas kīma is an assimilative preposition and conjunction, and they seem to share the same stem, kī-. This paper attempts to formulate the relationship between both particles, analysing data at several linguistic levels: (i) comparing their spelling and their morphological form with similar items shows kīma to be the bound form and kīam the accusative unbound form; (ii) from their respective notions and functions — manner, quality, degree, similarity, approximative, correlation and dependency, causality, purpose and locative — we learn that the particles share several of them; (iii) their apriori syntactic functions are disparate — kīma is the head of phrases, whereas kīam stands alone; (iv) by studying the affinity between the Mari particles qātamma ‘this way, similarly’ and qātam ša ‘like, as’, and contrasting them with kīam and kīma, it is shown, again, that kīma is the bound form of unbound kīam.